The Silences of Skåne: Sonic Representations of Space and Place in the Wallander Novels and Films - Huttunen, Kaapo (Walter de Gruyter GmbH, 2025)
The depiction of regional surroundings and natural conditions have often been seen as providing a sense of melancholy in Nordic noir, the distinctive form of crime fiction from the Nordic region, but also as a means to reflect the psychology of the characters and the socially critical themes of the narratives. In this regard, the Wallander novels, written by Henning Mankell (1948–2015), and also films and television series based on Mankell’s literature have often been given as prime examples. Thus far, however, sounds have not been taken into consideration in the matter. Sounds are an important factor in creating spatial experience and a sense of place in film, television, and literature. This article takes a comparative look at Wallander films and literature to examine sounds in the representation of Skåne, the main location of Wallander. It finds that characteristic regional sounds – especially silence, considered here a soundscape and a subjective spatial experience – play an important role in the Wallander novels but less so in the films, which leads to notable differences regarding the representation of Skåne and the characterisation of the main protagonist, Kurt Wallander, but also affects the narrative structure of the films.